Swallowing Outcomes for T1‐T4 Oropharyngeal Cancers Treated with TORS: Preliminary Experience. (23rd August 2013) - Ghanem, Tamer A.H.; Fei, Naomi; Simmerman, Erin; Lindholm, Jamie M.
Abstract : Objectives: 1) Assess swallowing function longitudinally using standardized questionnaires in a cohort of oropharyngeal cancer patients treated with transoral robotic surgery (TORS). 2) Compare the effect of tumor T‐stage on swallowing outcomes. Methods: A prospective, institutional review board (IRB)‐approved database of all patients undergoing TORS for oropharyngeal cancer at a tertiary‐care academic institution was queried from November 2010‐October 2012. Demographic data as well as longitudinal assessment of swallowing outcomes were collected. Standardized questionnaires included: University of Washington Quality of Life question 5 (UW‐QOLq5), MD Anderson Dysphagia Inventory (MDADI), and Functional Oral Intake Scale (FOIS). Two‐sided Wilcoxon signed‐rank tests were used to compare baseline values with corresponding 1, 3, 6, and 12 months post‐surgery. Two‐sided Wilcoxon rank‐sum tests were used to test for differences between T‐stages. Results: Thirty‐nine patients were studied with a mean age of 60.7 (42‐92). T‐stages included: T1 n = 14, T2 n = 15, T3 n = 6, T4 n = 4. No significant differences were detected at any time between patients with T1‐T2 and T3‐T4 stage disease on UW‐QOLq5, MDADI, or FOIS. Compared to baseline, UW‐QOLq5 measures were significantly lower at 1 month ( P = 0.0156), but not at 3 or 6 months. MDADI overall scores were significantly lower than baseline at 1 month ( P = 0.0134), but not at 3, 6, or 12 months. Compared to baseline, FOIS measures were significantly lower at 1 month ( P < .0001), and remained significantly lower at 3 ( P < .0001), 6 ( P < .0001), and 12 months ( P = 0.0039). Conclusions: Results suggests that while swallowing status declines immediately after TORS, it can be expected to approach baseline within 3 months post‐surgery.